Technology transfer of organic shredded beef to increase the economic value of processed Pinogu beef - Bambang Susilo; Hendrix Yulis Setyawan; Muhammad Arwani; Kiki Fibrianto; Yudin Yudiawan Maksum; Azwar Lahusin; Irwan Bempah; Wafa Nida Faida Azra; Riska Ayu Lestari; Rizki Putra Samudra; Arya Nugraha Hananto; Muhammad Bagaskara Wiratirta; Essa Noer Bhakty Mulia; Amelia Amelia; Fahmi Akbar Yuliansyah; I Kadek Olin Adi Wiguna; Djatmiko Bagus Wibowo (Community Empowerment, 2023)
Pinogu is a sub-district located in the Bogani Nani Wartabone National Park area, Gorontalo. Limited road access makes it difficult for the Pinogu community to sell organic cattle, which is one of Pinogu's main commodities. The purpose of this community service is to increase the knowledge and skills of the community in the Pinogu sub-district in processing organic beef into beef floss and fostering an entrepreneurial spirit in the business of making beef floss. The method used is training and mentoring with the early stages of designing tools (shredding machines and spinners), training on making beeaf floss, and assisting processing groups. This activity produces beef floss products with the name "SIBOGU" and a processing group with the name "KUB Mogulonga" consisting of mothers who are interested in participating in processing beef floss. This activity received positive support from the local government to assist with product licensing and marketing. In the future, it is hoped that the production process of beef floss can run sustainably and the cattle in Pinogu can have a more reasonable selling value.